2021
DOI: 10.1038/s41419-021-03897-0
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled receptor GPR17 inhibits glioma development by increasing polycomb repressive complex 1-mediated ROS production

Abstract: Glioma is the most common primary tumor in the central nervous system. However, the development of glioma and effective therapeutic strategies remain elusive. Here, we identify GPR17 as a potential target to treat glioma. Data mining with human LGG and GBM samples reveals that GPR17 is negatively correlated with glioma development. Overexpressing GPR17 inhibits glioma cell proliferation and induces apoptosis by raising ROS levels. GPR17-overexpressing glioma cells are less tumorigenic in the brain than in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The combinatorial treatment increased the production of ROS with 3.5-fold change in MMK1 and approximately 3.0-fold in JK2 cells. This result agreed with the previous data, that the overexpression of GPR17 stimulates apoptosis by inducing ROS production and thereby inhibits glioma cell proliferation [35]. This data also suggested that THTMP + T0 was more efficient in inducing ROS-mediated apoptosis.…”
Section: Thtmp + T0 Activates Intrinsic Pathways Of Apoptosis Inductionsupporting
confidence: 93%
“…The combinatorial treatment increased the production of ROS with 3.5-fold change in MMK1 and approximately 3.0-fold in JK2 cells. This result agreed with the previous data, that the overexpression of GPR17 stimulates apoptosis by inducing ROS production and thereby inhibits glioma cell proliferation [35]. This data also suggested that THTMP + T0 was more efficient in inducing ROS-mediated apoptosis.…”
Section: Thtmp + T0 Activates Intrinsic Pathways Of Apoptosis Inductionsupporting
confidence: 93%
“…Glioma, the most common type of brain tumor, has been divided into four groups based on malignancies [ 108 ]. Glioblastoma (GBM), also known as grade IV glioma, is one of the most aggressive forms of cancer [ 109 ].…”
Section: Brain and Nerve Tumorsmentioning
confidence: 99%
“…KLF9 decreased the expression of SOD1 , a protein needed for ROS clearance ( Figure 7 (1B)). Upregulation of GPR17 also decreased cAMP levels, indicating that glycolysis and lactate production were also decreased [ 108 , 114 ].…”
Section: Brain and Nerve Tumorsmentioning
confidence: 99%
“…Of note, glioma cell development has been concomitantly linked to aberrant activation of WNT signaling and dysregulation of GPR17 expression: WNT pathway genes overexpression has been associated with increased tumor growth and invasion via the maintenance of stemness leading to a poor prognosis in glioma patients; on the contrary, GPR17 levels in tumor samples are reduced, and its activation inhibits glioma formation. Thus the balance between WNT and GPR17 might be dysregulated in glioma [14,15] .…”
Section: Introductionmentioning
confidence: 99%